The Role of Generative Artificial Intelligence in the Success of Digital Project Management - Muntaha Manate Hashim (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Digital transformation has fundamentally altered administrative work through generative artificial intelligence (GAI), which enables human activity in developing novel content and creative solutions beyond existing paradigms. Specific Background: While GAI's theoretical frameworks are established globally, its integration with digital project management success within Arab administrative structures remains underexplored, particularly regarding how GAI dimensions interact with organizational efficiency. Knowledge Gap: Despite GAI's growing prominence, empirical evidence linking its specific dimensions—task definition, AI contribution, interaction methodology, AI structure, and human personality—to digital project management outcomes in developing economies is limited. Aims: This study investigates the relationship between GAI dimensions and digital project management success (organizational structure, technology, and digital innovation) among 188 employees at Iraq's Karbala Investment Authority using structural equation modeling. Results: GAI explains 43% of variance in digital project management success, with human personality (β=0.402), task definition (β=0.343), and AI contribution (β=0.278) showing significant positive effects, while interaction methodology and AI structure demonstrated non-significant impacts. Novelty: This research provides the first empirical Arabic-context framework demonstrating that human skills, behavior, and experience remain the primary drivers of digital project success when combined with GAI. Implications: Organizations must invest in behavioral and technical capabilities through command engineering training and digital simulation to bridge skills gaps and enable human-machine symbiosis for competitive advantage.Keywords : Generative Artificial Intelligence, Digital Project Management, AI Dimensions, Organizational Digital Transformation, Human-AI CollaborationHighlight : Human skills and behavior remain the primary driver of digital project success. Clear task definition significantly enhances AI-powered project automation and efficiency outcomes. AI contribution and human personality show stronger impact than technical infrastructure flexibility.